Significados alrededor del tejido de pelucas oncológicas en mujeres diagnosticadas con cáncer - Sanabria, Juan Pablo; Muriel, Andrea Stefanía; Parra, Nathalia (Psicooncología, 2017)
Fundament: Losing hair is a physical change that could affect the self-esteem of women with cancer. Objective: Understand the meanings behind the sewing of medical wigs in women diagnosed with cancer belonging to a self-help group in Cali (Colombia). Methodology: Interpretative phenomenological qualitative study in which 10 women participated. Preliminary results were presented in two focus groups composed of all members of the group who contributed to the analysis of the previously results collected in the 10 interviews. The data analysis was done with the support of Atlas.Ti program. Results: Participants described hair loss as a traumatic experience that involved high emotional impact. The use of accessories allowed to hide and reserved the disease. The motivations for linking the group were related to the opportunity to share experiences with other patients and with the desire to improve well-being in themselves and in women with cancer. Also, belonging to the group allowed to have a support network where they could express their fears and concerns. Conclusions: Although hair loss does not generate functional implications for the organism, it has been identified that this part of the body is related to social representations that includes the meaning of being a woman. The activity of sewing is presented as a therapeutic space where the participants can develop strategies for coping aspects of their life.